New proposed spherical slotted antenna covered by the layers of dielectric material and plasma - Osman Shakirovich Dautov; Mohammad Sadon AL-Abadi; Haidar N. Al-Anbagi (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The operation of the new proposed spherical slotted antenna covered by layers of dielectric material and plasma was analyzed numerically in this paper. By utilizing the Integra-functional equations method, the optimum thickness of dielectric material layer and suitable conditions which improve the operation of this antenna are analyzed here by MATHCAD. The thickness of dielectric layer must not be less or more than λ/6. Furthermore, the authors propose manipulating the operation frequency to enable such antenna to work in most circumstances.